Stress-resilient maize hybrid adoption factors and impact: Evidence from rain-fed agroecologies of Karnataka state, India - Kulkarni, Atul P.; Kuchanur, Prakash H.; Satihal, Dayanand G.; Zaidi, P. H.; Rahut, Dil Bahadur (Frontiers in Sustainable Food Systems, 2022)
Drought is one of the major abiotic constraints that adversely affect maize production in the rain-fed agro-environment in the Asian tropics. In view of the recurrent drought, stress-resilient (SR) maize hybrids were developed and deployed to minimize yield penalties and ensure minimum sustainable production of maize in mild to severe drought conditions. Data were collected from 180 farmers from two districts of northern Karnataka. Findings suggest that the household location, caste, access to credit, number of extension visits, and participation in field days significantly influence the adoption of the SR maize hybrid in the study area. The inverse probability weighting (IPW) estimator revealed that households adopting SR maize hybrid have higher yield and income (23% more yield and $137.86/ha more net income) than the non-adopters. As the SR maize hybrid has considerable scope for improving the livelihood and security of farmers, the agricultural policy should support and scale the stress-resilient maize hybrids in the region.